Clinical significance of circulating tumor cells detection in renal cell carcinoma with thrombus: A STROBE-compliant study. Issue 22 (29th May 2020) - Ge, Liyuan; Song, Yimeng; Yang, Feilong; Zhao, Guojiang; Lu, Min; Zhang, Shudong; Ma, Lulin
Abstract : Abstract: The aim of the study was to evaluate the potential role of circulating tumor cell (CTC) detection in the surgical assessment of renal cell carcinoma (RCC) patients with thrombi. Nine patients diagnosed with renal mass and thrombi were enrolled from June 2018 to January 2019. Blood samples were collected for CTC detection using SE-iFISH assay. CD45, DAPI, programmed death ligand 1, and fluorescence in situ hybridization with the centromere of chromosome 8 (CEP8) were immune-stained for analysis. Patient demographics, clinical features, pathological characteristics, and CTC detection results were extracted for analysis. Seven of 9 patients (77.8%) had 12 detectable CTCs, 5 of which were with CEP8-positive signal ≥5 and the others were CEP8-positive signal = 3. All 3 patients (100%) with IVC invasion had detectable CTCs, whereas CTCs were detected in 4 of 6 patients (66.7%) without IVC invasion. CEP8 analysis revealed that CTCs in IVC invasion patients were all of CEP8-positive signal ≥5 status, whereas only half of the CTCs in patients without IVC invasion were of CEP8-positive signal ≥5 pattern. In conclusion, both CTC subtype and total CTC number may serve as a marker for predicting inferior vena cava invasion in RCC patients.